EFFECT OF ORAL VITAMIN D SUPPLEMENTATION ON PSORIASIS SEVERITY: DOES IT GENERATE SIGNIFICANT BENEFITS? EFECTO DE LA SUPLEMENTACIÓN ORAL CON VITAMINA D SOBRE LA GRAVEDAD DE LA PSORIASIS: ¿GENERA BENEFICIOS SIGNIFICATIVOS? - Ospina Gómez, Juan Esteban (2024)
Psoriasis is a chronic immune-mediated skin disease with a complex genetic and pathogenic basis, often leading to significant comorbidities and a reduced quality of life. Its prevalence varies globally and exhibits an increasing trend over time. Comorbidities such as psoriatic arthritis, cardiovascular diseases, and mental health issues further compound the burden of psoriasis. Treatment options range from topical therapies to systemic agents, with biologics playing a prominent role in recent years. However, the safety and efficacy of these treatments are continuously assessed through real-world data. Vitamin D has gained attention as a potential therapeutic target due to its role in immune regulation and skin barrier function. This review aims to evaluate the efficacy of oral vitamin D supplementation in ameliorating the severity of psoriasis. After bibliographic search, it was found that psoriasis is a multifaceted condition with significant global implications. Biologics have transformed its management, and oral vitamin D supplementation is a promising avenue for further exploration. A comprehensive, patient-centered approach that considers comorbidities and long-term outcomes is crucial for optimizing psoriasis care. Further research is needed to fully understand the role of vitamin D in psoriasis and its potential as a therapeutic intervention.